Functional near‐infrared spectroscopy to probe sensorimotor region activation during electrical stimulation‐evoked movement. (7th November 2017) - Muthalib, Makii; Ferrari, Marco; Quaresima, Valentina; Kerr, Graham; Perrey, Stephane
Summary: This study used non‐invasive functional near‐infrared spectroscopy (fNIRS) neuroimaging to monitor bilateral sensorimotor region activation during unilateral voluntary (VOL) and neuromuscular electrical stimulation (NMES)‐evoked movements. Methods. In eight healthy male volunteers, fNIRS was used to measure relative changes in oxyhaemoglobin (O2 Hb) and deoxyhaemoglobin (HHb) concentrations from a cortical sensorimotor region of interest in the left (LH) and right (RH) hemispheres during NMES‐evoked and VOL wrist extension movements of the right arm. Results. NMES‐evoked movements induced significantly greater activation (increase in O2 Hb and concomitant decrease in HHb) in the contralateral LH than in the ipsilateral RH (O2 Hb: 0·44 ± 0·16 μM and 0·25 ± 0·22 μM, P = 0·017; HHb: −0·19 ± 0·10 μM and −0·12 ± 0·09 μM, P = 0·036, respectively) as did VOL movements (0·51 ± 0·24 μΜ and 0·34 ± 0·21 μM, P = 0·031; HHb: −0·18 ± 0·07 μΜ and −0·12 ± 0·04 μΜ, P = 0·05, respectively). There was no significant difference between conditions for O2 Hb ( P = 0·144) and HHb ( P = 0·958). Conclusion. fNIRS neuroimaging enables quantification of bilateral sensorimotor regional activation profiles during voluntary and NMES‐evoked wrist extension movements.